Supporting satisfaction, satisfying support: Bidirectional associations of social support and life satisfaction - CHIA, Jonathan Louis Jie Sheng (Institutional Knowledge at Singapore Management University, 2024)
Existing literature has explored the impact of social support (SS) on life satisfaction (LS). However, the reciprocal relationship—that is, the influence of LS on SS—remains understudied, despite extant theoretical support. In addressing this gap, the present study employed bivariate latent growth modeling to examine bidirectional associations between SS and LS trajectories among 8,449 middle-aged and older adults in Singapore, over seven waves spanning almost 6 years. Results provided evidence supporting the notion of bidirectional associations. Specifically, baseline SS positively predicted subsequent changes in LS, and baseline LS positively predicted subsequent changes in SS. Findings underscore the potential for interventions and policies aimed at enhancing well-being among older individuals to capitalize on this bidirectional relationship. By targeting either LS or SS, interventions could potentially trigger positive feedback loops, amplifying their collective impact on overall well-being.